Off to the fair - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Two international fairs on agriculture and animal resources will be held in West Africa soon. SARA (for the Salon international de l'agriculture et des ressources animales) will be held by the Ministry of Agriculture in Abidjan (Côte d'Ivoire) from...